Landslide Mitigation in Cianjur Regency Through Satellite Imagery-Based Mapping - Maarif, Syaiful; Iryanti, Mimin; Agustine, Eleonora (TECHNO: JURNAL PENELITIAN, 2025)
Indonesia is a country with a high frequency of natural disasters due to its location in the tropics and along the pacific ring of fire. Its diverse topography, characterized by numerous mountains and coastal areas, significantly influences land slopes. One common disaster associated with slope differences is landslides-mass movements of soil triggered by various factors, one of which is the steepness of the slope. Cianjur Regency is among the regions with a high risk of landslides. According to data from the West Java Regional Disaster Management Agency (BNPB), Cianjur experiences more than 90 landslides annually. Therefore, mitigation efforts must be carried out based on landslide risk mapping in this region. The purpose of this research is to identify and map landslide-prone areas in Cianjur Regency. Mapping results from 2018 to 2023 indicate that areas with the highest landslide risk are concentrated in northern Cianjur, particularly in the districts of Cugenang, Cipanas, Sukaresmi, and surrounding areas. Mitigation efforts should be prioritized in these districts without neglecting other areas. In addition to the 2018–2023 mapping, a 2025 prediction map can also be developed to guide broader and more comprehensive mitigation efforts, which still indicate a very high risk in northern Cianjur. Furthermore, mapping using the SMORPH method has produced results that closely align with both the annual and predictive mapping approaches, reinforcing the validity of the identified high-risk zones.